Kewajiban Penyertaan Kartu BPJS Kesehatan Pada Transaksi Jual Beli Tanah dan Bangunan dalam Rangka Optimalisasi Program BPJS (Studi Inpres Nomor 1 Tahun 2022 Tentang Optimalisasi Pelaksanaan Program Jaminan Kesehatan) - Saputra, Muhamad Aditya; Musyafah, Aisyah Ayu (Universitas Ekasakti, 2023)
To optimize the implementation of the national health insurance program (JKN), increase accessibility to quality medical services, and ensure the sustainability of the JKN program, President Joko Widodo issued Presidential Instruction (Inpres) no. One of 2022 concerning optimizing the implementation of the JKN program which was issued on January 6, 2022 The Minister of ATR/BPN was instructed by the president to guarantee that applicants for registration of transfer of land rights due to a sale and purchase are those who are active participants in the JKN program. The research method in this study is a type of normative legal research. Through the study of literature and other legal materials, the material is then analyzed through legal interpretation both functionally and teleologically and then conclusions will be drawn using the deductive method. The conclusion is that in selling land purchases without including the BPJS Health card, it is still valid based on PP no. 24 of 1997, but as an effort to make the JKN program optimally sustainable, the government also implies the BPJS Health card as a requirement in buying and selling land.